Simulation of human diving - Wooten, W. L.; Hodgins, J. K. (1996)
In this paper we describe a dynamic model and control System for a human platform diver. The dynamic model is a 38 degree-of-freedom rigid body model with dynamic Parameters similar to those given. in the literature for humans. The control System uses a state machine, algorithms for balance, and proportional derivative servis to balance the model on a 10 meter platform, to generate the angular velocity for the dive, and to perform the maneuvers required during the dive. The motion of the simulated divers closely resembles video footage of dives performed by human athletes. The control and simulation techniques presented in this paper will be useful for analysis of sports performance and to as a source of realistic motion for synthetic actions.